The Effect of WO3-doped soda lime silica SLS waste glass to develop lead-free glass as a shielding material against radiation - Mustafa, Iskandar Shahrim; Abdul Rahman, Azhar; Mohd Zaid, Mohd Hafiz; Hisam, Rosdiyana; Abdul Malik, Muhammad Fadhirul Izwan; Mohd Shariff, Hanisha (Multidisciplinary Digital Publishing Institute, 2022)
The current study aims to enhance the efficiency of lead-free glass as a shielding material against radiation, solve the problem of the dark brown of bismuth glass, and reduce the accumulation of waste glass disposed in landfills by using soda-lime-silica SLS glass waste. The melt-quenching method was utilized to fabricate (WO3)x [(Bi2O3)0.2 (ZnO)0.3 (B2O3)0.2 (SLS)0.3]1−x at 1200 °C, where x = (0, 0.01, 0.02, 0.03, 0.04, and 0.05 mol). Soda lime silica SLS glass waste, which is mostly composed of 74.1 % SiO2, was used to obtain SiO2. Radiation Attenuation parameters were investigated using narrow-beam geometry and X-ray fluorescence (XRF). Furthermore, the parameters related to radiation shielding were calculated. The results showed that when WO3 concentration was increased, the half-value layer was reduced, whereas the μ increased. It could be concluded that WBiBZn-SLS glass is a good shielding material against radiation, nontoxic, and transparent to visible light.